1993
DOI: 10.1037/h0079422
|View full text |Cite
|
Sign up to set email alerts
|

Mental health status of Cambodian refugees ten years after leaving their homes.

Abstract: The mental health status of a general population sample of Cambodian refugees living in the United States was assessed ten years after they had left their homes in Cambodia. Subjects were found to be experiencing extremely high levels of post-traumatic stress disorder, dissociation, depression, and anxiety. Ninety percent of these refugees exhibited marked symptomatology in one or more of these categories.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
1
4

Year Published

1995
1995
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(48 citation statements)
references
References 20 publications
2
41
1
4
Order By: Relevance
“…Previous empirical investigations have found that depression and posttraumatic stress disorder (PTSD) constitute the most common psychiatric disorders in refugee populations (Marshall, Schell, Elliot, Berthold, & Chun, 2005). In one study, 86% of Cambodians participants met DSM-III-R criteria for PTSD and 80% met the criteria for depression (Carlson & Rosser-Hogan, 1993). Even after more than 20 years since the fall of the Khmer Rouge and immigration to the United States, Cambodian Americans are still suffering from extremely elevated rates of depression (51%) and other mental disorders (Marshall et al, 2005).…”
Section: Mental Health Issuesmentioning
confidence: 99%
“…Previous empirical investigations have found that depression and posttraumatic stress disorder (PTSD) constitute the most common psychiatric disorders in refugee populations (Marshall, Schell, Elliot, Berthold, & Chun, 2005). In one study, 86% of Cambodians participants met DSM-III-R criteria for PTSD and 80% met the criteria for depression (Carlson & Rosser-Hogan, 1993). Even after more than 20 years since the fall of the Khmer Rouge and immigration to the United States, Cambodian Americans are still suffering from extremely elevated rates of depression (51%) and other mental disorders (Marshall et al, 2005).…”
Section: Mental Health Issuesmentioning
confidence: 99%
“…The overall DES score is obtained by averaging the 28 item scores, yielding a score ranging from 0 to 100. Scores above 20 suggest the presence of highly dissociative experiences and that further clinical assessment is warranted, whereas scores below 10 fall within the normal range of dissociative experiences (Carlson & Rosser-Hogan, 1993). The DES has been to shown to have very good validity and reliability, and good overall psychometric properties in a number of studies (see Briere, 1997 for a review).…”
Section: Pennebaker Inventory Of Limbicmentioning
confidence: 99%
“…Enerzijds maakten de onderzoekers gebruik van verschillende methoden, zoals statusonderzoek (Kuch & Cox, 1992 ), vragenlijsten (Carlson & Rosser-Hogan, 1993 ;Southwick et al, 1993 ) en gestructureerde klinische interviews (Green, 1993 ;North et al, 1994 ;Roszell et al, 1991 ). Anderzijds lijkt het waarschijnlijk dat psychogene amnesie moeilijk te achterhalen is.…”
Section: Inleidingunclassified
“…Al eerder werd gesignaleerd dat de prevalentiecijfers van psychogene amnesie fors uiteenlopen. Verschillende onderzoekers (Carlson & Rosser-Hogan , 1993 ;Southwick et al, 1993) vroegen de onderzochte patie¨nten eenvoudigweg of het zo was dat zij zich gedeelten van de traumatische gebeurtenis niet wisten te herinneren. Het voorafgaande doet vermoeden dat deze manier van onderzoeken niet toereikend is.…”
Section: Conclusie En Aanbevelingenunclassified